Implikasi Konseling Adiksi Non-Zat sebagai Upaya Preventif terhadap Gangguan Psikososial dalam Komunitas Hobi - Galih Fajar Fadillah; Jarir Idris; M. Agus Wahyudi (STAI Al-Mujtama Pamekasan, 2026)
This study aims to describe the process and effectiveness of non-substance addiction counseling as a preventive measure against potential psychosocial disorders in the El-Jemblink Meisya Holiday Community. The method used is a qualitative case study with data collection techniques through participatory observation, in-depth interviews, and documentation of several community members who show a tendency towards addictive behavior towards community activities, such as excessive smartphone use, time management, and emotional dependence on social recognition. The results of the study showed that the implementation of addiction counseling was able to increase self-awareness, emotional regulation, and more adaptive decision-making abilities in participants. This preventive effort also strengthens the function of the community as a healthy social development space, not just a place of psychological escape. This study recommends the need for integration of psychosocial assistance programs in hobby communities to prevent the development of non-substance addictive behavior